An assessment of contamination pickup on ground robotic vehicles for nuclear surveying application. (1st June 2021) - Banos, A; Hayman, J; Wallace-Smith, T; Bird, B; Lennox, B; Scott, T B
Abstract: Ground robotic vehicles are often deployed to inspect areas where radioactive floor contamination is a prominent risk. However, the accuracy of detection could be adversely affected by enhanced radiation signal through self-contamination of the robot occurring over the course of the inspection. In this work, it was hypothesised that a six-legged robot could offer advantages over the more conventional ground robotic devices such as wheeled and tracked rovers. To investigate this, experimental contamination testing and computational Monte Carlo simulation techniques (GEANT4) were employed to understand how radioactive contamination pick-up on three different robotic vehicles would affect their detection accuracy. Two robotic vehicles were selected for comparison with the hexapod robot based on their type of locomotion; a wheeled rover and a tracked rover. With the aid of a non-toxic fluorescent tracer dust, the contamination received by the all three vehicles when traversing a contaminated area was initially compared through physical inspection using high definition cameras. The parametric results from these tests where used in the computational study carried out in GEANT4. A cadmium zinc telluride detector was simulated at heights ranging from 10 to 50 cm above each contaminated vehicle, as if it were mounted on a plinth. Assuming a uniform activity of 60 Bq cm −2 on all contaminated surfaces, the results suggested that due to the hexapod's small ground-contacting surface area and geometry, radiation detection rates using an uncollimated detector are likely to be overestimated by between only 0.07%–0.12%, compared with 3.95%–8.43% and 1.75%–14.53% for the wheeled and tracked robot alternatives, respectively.